Fenofibrate Nano-Eyedrops Ameliorate Retinal Blood Flow Dysregulation and Neurovascular Coupling in Type 2 Diabetic Mice - Junya Hanaguri; Noriaki Nagai; Harumasa Yokota; Akifumi Kushiyama; Masahisa Watanabe; Satoru Yamagami; Taiji Nagaoka (MDPI AG, 2022)
We investigated the effect of fenofibrate nano-eyedrops (FenoNano) on impaired retinal blood flow regulation in type 2 diabetic mice. Six-week-old db/db mice were randomly divided into an untreated group (n = 6) and treated group, which received FenoNano (n = 6). The longitudinal changes in retinal neuronal function and blood flow responses to systemic hyperoxia and flicker stimulation were evaluated every 2 weeks in diabetic db/db mice treated with FenoNano (n = 6) or the vehicle (n = 6) from ages 8-14 weeks. The retinal blood flow was assessed using laser speckle flowgraphy. We also evaluated the expressions of vascular endothelial growth factor (VEGF), glial fibrillary acidic protein (GFAP), and aquaporin 4 (AQP4) and the phosphorylation of peroxisome proliferator-activated receptor alpha (PPAR-α) by immunofluorescence. In db/db mice treated with FenoNano, both responses were restored from 8 to 14 weeks of age compared with the diabetic mice treated with the vehicle. At 14 weeks of age, the impaired regulation of retinal blood flow during systemic hyperoxia and flicker stimulation improved to about half of that in the db/db mice treated with FenoNano compared with the db/m control group (n = 5). FenoNano prevented the activation of VEGF and GFAP expression and increased the AQP4 expression and the phosphorylation of PPAR-α detected by immunofluorescence compared with the diabetic mice treated with the vehicle eyedrop. Our results suggested that the fenofibrate nano-eyedrops prevent retinal glial dysfunction via the phosphorylation of PPAR-α and improves the retinal blood flow dysregulation in type 2 diabetic mice.